Deskripsi perilaku prososial pada anak-anak muda dengan cacat intelektual di Nusa Tenggara Timur - Kiling-Bunga, Beatriks Novianti; Ngawas, Kresensia Wea Aga; Kiling, Indra Yohanes (Konsorsium Psikologi Ilmiah Nusantara, 2016)
World Health Organization and United Nations Children’s Fund havestated in year 2012 that one of their global agenda is to fulfill the needs of inclusive Early Childhood Care and Development (ECCD) to increase the participation and development of young children with disabilities. One of important things for the agenda are understanding various special needs of young children with various kind of mental disability, such as mental retardation or nowadays known as intellectual disability. This research aims to narratively describe the prosocial behaviors of a young child with intellectual disability in special school of Pembina Kupang, East Nusa Tenggara. This research used qualitative approach with child observation and interview to the parents as the main technique to gather data. This research shows that prosocial behaviors in young children with intellectual disability are divided into four aspects, those are: a) the ability to join groups, b) supportive acts, c) empathy and caring, and d) self-adjustment. These behaviors were shown in the child’s dailyactivities, her habits, affected by the culture and daily activities of her parents and siblings, and also by the interaction with her friends and family. This research could give important information about the importance of managing the social interaction in inclusive ECCD by putting emphasis in four aspects described above, and also the role of parents and ECCD tutors in facilitating activities that could help stimulate specific needs of social skills in young children with intellectual disability.